The impacts of the pandemic for the teacher in initial formation: The view of undergraduates - Littke, Bruna Vieira Bardt; Lohn, Luciana Gelsleuchter; Barcellos , Michelle (Seven Editora, 2023)
With the arrival of the pandemic, sudden changes happened in education, forcing teachers and students to live in a new format of classes. These changes, without much planning, end up generating some effects, expected and not expected. This research aims to demonstrate the transformations that the pandemic has brought to the Degree in Chemistry course of the Federal Institute of Santa Catarina - Câmpus São José (IFSC - SJ), observed by the students. In this way, it aims to be able to observe its positive and negative points, and results of the transformations that occurred in the first year of the pandemic, the first and second semesters of 2020. In pursuit of this objective, 29 teachers in initial training at the institution were interviewed through questionnaires, where it was possible to perceive that the effects of the pandemic go far beyond the classroom and that they are reflected in the students’ learning. It is concluded, after analysis of the data of the research, together with the bibliographic studies, that, even if amid different perspectives, due to the reality of each student, most of the interviewees were partially satisfied with the methodologies used in the period. And despite adverse results, the actions taken in the face of the pandemic have provided knowledge that will serve as the basis for the teacher training of these students. However, even bringing benefits, taking into account the emergency nature, they demand improvements to the environment. DOI: https://doi.org/10.56238/devopinterscie-288